TRADISI SLAMETAN PENGELING-ELING MASYARAKAT HINDU KABUPATEN BLITAR: PRAKTEK HARMONISASI DENGAN LELUHUR - Sujaelanto (Widya Aksara : Jurnal Agama Hindu, 2025)
Death is a certainty experienced by every living creature, including humans. In the Hindu belief system, the Spirit that leaves the physical body will be followed by its karma wasana and will have an impact on rebirth (punarbawa). The process of the spirit's journey after leaving the physical body, for Hindus in Blitar will be given respect through a thanksgiving. The death thanksgiving begins on the first day of death until the thousandth day, and some people still continue the death thanksgiving after a thousand days, which is known as the pengeling-eling thanksgiving which has no end. This phenomenon is the reality of the Hindu community in Blitar Regency in carrying out the teachings of pitra yadnya. The Selamten tradition is one of the rituals of people aimed at asking for safety in the form of a feast event. The salvation ritual becomes the soul in the lives of Javanese Hindus. Pengeling eling is a death thanksgiving ritual after the thousand-day thanksgiving event and is carried out to coincide with the pancawara, sapta wara and sasih days of death. The series of pengeling-eling includes nyekar, offerings and a feast event. The Nyekar event is held at the grave by scattering flowers and boreh and reciting prayers to the ancestors using Javanese. The offerings event is held before the kenduri procession which is held in a certain place by offering various foods, drinks and prayers carried out by one of the family representatives. The kenduri event is the peak event of the southern pengeling-eling. Kenduri invites close neighbors to witness the pengeling-eling. Prayers are read by the tukang ujub and after finishing reciting the prayers, the offerings given by the prayer are divided equally to the guests who are present to be eaten together and the sides are taken home in the form of blessings. The series of pengeling-eling events include various flower, fruit, drink and food facilities complete with ingkung arranged into an ambeng. The pengeling-leing celebration facilities are a reflection of pitra yadnya in Hindu teachings. The completeness of the facilities used in the pengeling-eling event is only as a mediation for spiritual communication between the living family and the deceased. Verbal communication is carried out by reciting the pengeling-eling prayers.